Shape Memory Alloy (SMA) connectors for ultra-high vacuum applications: modeling and testing - Giovinco, Valentina; Maletta, Carmine; Garion, Cedric; Mundo, Domenico (Università della Calabria, 2024)
Shape Memory Alloy (SMA) connectors have been developed at CERN in recent years for Ultra-High-Vacuum (UHV) applications in the Large Hadron Collider (LHC) as an alternative to the traditional coupling provided by metallic flanges tightly connected by several screws or heavy collars. SMA couplers offer many advantages, including low cost, compact size, ease of assembly and maintenance, ability to make bi-material connections, and ability to be remotely controlled by temperature variation, limiting the need for human presence in highly radioactive areas of the accelerator. The working principle of a SMA connector is based on thermoelastic martensitic transformations between two crystallographic structures, austenite and martensite. The object of this project is the testing and modelling of SMAs in order to investigate and describe the macroscopic behaviour of the material. Methods and measurements of an extensive experimental campaign on Nickel-Titanium (NiTi) alloy specimens are herein presented and discussed. Different stress and temperature conditions are investigated, as well as the thermomechanical training of different shaped connectors (rings, ovals, C-shaped) and the constrained recovery capability of ring couplers. Two analytical models based on the elastic-plastic theory of axial-symmetric bodies have been developed to describe the pre-expansion and constrained recovery of SMA rings. Systematic comparisons between the analytical predictions with Finite Element Analysis (FEA) and experimental measurements show very good agreement. Finally, SMA constitutive modelling and FE simulations by a user-defined material model have been performed. Models and results are herein presented. This thesis provides robust tools to be used for the design of SMA couplers with shape recovery capabilities. Keywords: Shape memory alloys, NiTi alloys, vacuum connections, constrained recovery.
UNIVERSITY OF CALABRIA. Dipartimento di Ingegneria Meccanica, Energetica e Gestionale. Dottorato in Ingegneria Civile e Industriale, Ciclo XXXV
Keywords: shape memory alloys; NiTi alloys; vacuum connections; constrained recovery